Variations in Pedicel Structural Properties Among Four Pear Species (Pyrus): Insights Into the Relationship Between the Fruit Characteristics and the Pedicel Structure - Cui, Zhenhua; Sun, Haoqi; Lu, Yuqin; Ren, Lixin; Xu, Xinrui; Li, Dingli; Wang, Ran; Ma, Chunhui (Frontiers in Plant Science, 2022)
Fruit pedicel is the bridge linking the parent tree and the fruit, which is an important channel for water and nutrients transport to the fruit. The genetic specificity determines the characteristics of the pedicel and the fruit, but the relationship between pedicel structure and the fruit characteristics is unexplored. Combining the fruit characteristics investigation, the statistical analysis of the pedicel structural properties, and the 2-D and 3-D anatomical observation of the pedicel, the present study found distinctive contributions of the pedicel elements to the fruit characteristics in four pear species. The European pear (Conference) showed distinct fruit shape index and pedicel structural properties compared with the oriental pears (Akizuki, Yali, and Nanguoli). The fruit size positively correlated to pedicel length, fiber area, pedicel diameter, the area percentage of the cortex, and the area percentage of phloem; however, fruit firmness and soluble solids concentration are showed a stronger positive correlation to xylem area, pith area, the area percentage of xylem, the area percentage of sieve tube, and the area percentage of pith. Pedicel elements, pith, fiber, and cortex, likely play a certain role in fruit growth due to the variations of their characteristics demonstrated in the four pear species. The porosity, the ratio of the surface area to the volume, and the spatial arrangement of the vessels showed significant variations across the pear species, indicating the distinction of the hydraulic conductance of the pedicels. Our findings provided direct evidence that pedicel structural elements contributed distinctively to the fruit characteristics among pear species.